A 48-MW floating photovoltaic design and integration to a grid - Adrianti Adrianti; Thoriq Kurnia Agung; Muhammad Nasir; Pinto Anugrah (Institute of Advanced Engineering and Science, 2023)
Photovoltaic is one of the renewable power sources with the highest growth in recent decades. However, large photovoltaic capacities require enormous areas for installing the modules, which is frequently troublesome. This issue could be addressed by a floating photovoltaic system since it can be installed on the surface of unutilised lakes, and dams. This study aims to design a 48-MW floating photovoltaic at Lake Singkarak and determine a connected substation to the West Sumatra Grid. PVsystem and digsilent powerfactory were used in this study as the calculation and simulation tools. The study’s results discover that the 48-MW floating photovoltaic design consists of 96,000 photovoltaic modules of 500 Wp and 16 inverters of 3,000 kVA. Simulation results showed that Solok substation is the most optimum choice to connect the floating PV, as it provides better voltage profiles, fewer power losses and a shorter distance. The harmonic simulation also showed the THDv of 2.14% at 150 kV of Solok substation, which is still within acceptable limits.